Thông tin và nghiên cứu khoa học - Phạm, Thị Phương Thùy (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
Analysing the nature of information in the research process. Identifying the role of information resource in supporting research. Analysing the relationship between the information officers and researchers in the scientific information activity environment.